Value of random urinary calcium to creatinine ratio in diagnosing hypercalciuria in children with nocturnal enuresis - AL-Zwaini, Isam J.; Obaid*, Ali A.R; Obaid*, Ali A.R; Gatia, Abbas M.; Marzook, Ahmed A. (AL-Kindy College Medical Journal, 2016)
Background:Nocturnal Enuresis is a common problem affecting 20% of five years old children and up to 2% of adolescent and young adult. Although it is a self limiting benign condition, it has social and psychological impact on the child and his family. Many pathophysiological theories had been suggested, but none is confirmed. Hypercalciuria has been suggested to be associated with higher incidence of nocturnal enuresis. Objectives:The aim of our study to test the value of Ca/Cr ratio, on random urine sample, in diagnosing hypercalciuria in enuretic children. Type of study: Cross sectional study.Methods:Forty four enuretic children were enrolled in this study and forty five children without nocturnal enuresis were taken as control group. Results:The prevalence of abnormal Ca/Cr ratio was higher among enuretic children when compared with control group; the result was statistically significant (P. value0.002). Among the enuretic children, higher Ca/ Cr ratio was statisticallyassociated with urinary symptoms, abnormal general urine examination, and positive family history. Nosuch association was found with the gender or frequency of bed wetting per week. Conclusions:the results of this study suggest that hypercalciuria has a significant association with NE, rendering routine screening of hypercalciuria by Ca/Cr ratio on a random urine sample, is reasonable. Furthermore, a large scale studies are needed to confirm the role of low calcium diet, and other measures in treatment of idiopathic hypercalciuria, in the management of enuretic children with abnormal Ca/Cr ratio